Split application of polymer-coated urea combined with common urea improved nitrogen efficiency without sacrificing wheat yield and benefits while saving 20% nitrogen input - Ma, Quan; Tao, Rongrong; Jia, Wenxin; Zhu, Min; Ding, Jinfeng; Li, Chunyan; Guo, Wenshan; Zhou, Guisheng; Zhu, Xinkai (Frontiers in Plant Science, 2024)
Controlled-release nitrogen fertilizer (CRNF) has been expected to save labor input, reduce environmental pollution, and increase yield in crop production. However, the economic feasibility is still controversial due to its high cost. To clarify the suitable application strategy of CRNF in promoting the yield, nitrogen use efficiency and income on wheat grown in paddy soil, four equal N patterns were designed in 2017-2021 with polymer-coated urea (PCU) and common urea as material, including PCU applied once pre-sowing (M1), PCU applied 60% at pre-sowing and 40% at re-greening (M2), 30% PCU and 30% urea applied at pre-sowing, 20% PCU and 20% urea applied at re-greening (M3), and urea applied at four stage (CK, Basal:tillering:jointing:booting=50%:10%:20%:20%). In addition, M4-M6, which reduced N by 10%, 20% and 30 % respectively based on M3, were designed in 2019-2021 to explore their potential for N-saving and efficiency-improving. The results showed that, compared with CK, M1 did not significantly reduce yield, but decreased the average N recovery efficiency (NRE) and benefits by 1.63% and 357.71 CNY ha -1 in the four years, respectively. M2 and M3 promoted tiller-earing, delayed the decrease of leaf area index (LAI) at milk-ripening stage, and increased dry matter accumulation post-anthesis, thereby jointly increasing spike number and grain weight of wheat, which significantly increased yield and NRE compared with CK in 2017-2021. Due to the savings in N fertilizer costs, M3 achieved the highest economic benefits. With the 20% N reduction, M5 increased NRE by 16.95% on average while decreasing yield and net benefit by only 6.39% and 7.40% respectively, compared with M3. Although NRE could continue to increase, but the yield and benefits rapidly decreased after N reduction exceeds 20%. These results demonstrate that twice-split application of PCU combined with urea is conducive to achieving a joint increase in yield, NRE, and benefits. More importantly, it can also significantly improve the NRE without losing yield and benefits while saving 20% N input.